Simply effective : how to cut through complexity in your organization and get things done - Ashkenas, Ronald N. (Harvard Business Press, 2010)
Trying to get things done in organizations can feel like trying to swim in cement. But complexity doesn't happen all on its own managers unwittingly create complexity all the time. So while complexity in the outside environment isn't going to go away, the good news is that managers can reduce it. This book shows managers how to do so.